2019
DOI: 10.3390/f10080701
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Terrestrial Photogrammetry for Street Tree Mapping and Measurements

Abstract: Urban forests are often heavily populated by street trees along right-of-ways (ROW), and monitoring efforts can enhance municipal tree management. Terrestrial photogrammetric techniques have been used to measure tree biometry, but have typically used images from various angles around individual trees or forest plots to capture the entire stem while also utilizing local coordinate systems (i.e., non-georeferenced data). We proposed the mobile collection of georeferenced imagery along 100 m sections of urban roa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…TP as a passive remote sensing, is easy to be influenced by light and surrounding environment [54,55]. TP has a weak ability to obtain information about branches or tree canopy [56]. As an active remote sensing technology, TLS can be sampled point by point.…”
Section: Limitations and Application Potentialmentioning
confidence: 99%
“…TP as a passive remote sensing, is easy to be influenced by light and surrounding environment [54,55]. TP has a weak ability to obtain information about branches or tree canopy [56]. As an active remote sensing technology, TLS can be sampled point by point.…”
Section: Limitations and Application Potentialmentioning
confidence: 99%
“…Thus, aerial imagery (hyperspectral, RGB or PPC) may play an important role in tree mapping, both in the characterization and delineation of tree crowns and in species identification, since these data have enough spectral and spatial resolution [29,81,102]. However, Katz et al [11] reported that one of the main limitations of aircraft aerial imagery is the reduced availability of these images over time, given that images are taken at specific times, making it difficult to analyze vegetation at different phenological stages.…”
Section: Aerial Imagerymentioning
confidence: 99%
“…Meanwhile, although hyperspectral information from aerial images represent a valuable resource for species identification through spectral signatures and shape study, several studies showed that two individuals of the same species may have different spectral and structural characteristics due to the growth form and phenology [93,102]. Another limitation regarding the use of aerial images in the identification of trees in the city is the heterogeneity of the landscape where elements, such as facades, roofs, and others can be mistaken for trees or partly hide them [5], in addition to objects adjacent to the trees that can lead to misclassifications when using PPCs [100,103].…”
Section: Aerial Imagerymentioning
confidence: 99%
“…The images were acquired approximately 3.5 m above the ground with the platform moving at 0.5 m/sec providing 70% image overlap and 60% sidelap. This configuration allows for photogrammetric analysis of the images to produce point clouds, orthoimages, and Digital Surface Model (DSM) [35,36]. The four beds adjacent to those containing the plots (two from each side) were also surveyed to provide overlapping images for the photogrammetric analysis as shown in Figure 1.…”
Section: Image Data Acquisition and Preprocessingmentioning
confidence: 99%